BT-6 CLINICO-RADIO-PATHOLOGICAL FEATURES OF 1ST RELAPSE OF GLIOBLASTOMA AFTER PHOTODYNAMIC THERAPY. (3rd December 2022) - Yoshioka, Yamato; Akimoto, Jiro; Fukami, Shinjiro; Nagai, Kenta; Saitou, Yuuki; Kohno, Michihiro
Abstract: Introduction: We describe the clinicopathological picture of patients who underwent surgery at the time of initial recurrence after photodynamic therapy (PDT) for first-episode glioblastoma. Subjects and Methods: We examined the clinicopathological picture of 12 patients who had undergone PDT in a sub-total or greater resected luminal wall at the time of initial surgery, and who were able to undergo repeat resection because a new contrast-enhancing lesion was detected during follow-up. Results: The age at onset ranged from 43 to 80 years, with a male-to-female ratio of 9:3. PDT was applied to the wall of the resected lumen 4-13 times using a reflector as needed. Initial pathology showed IDH wild-type glioblastoma in all patients. Postoperatively, only the Stupp regimen was performed, but local recurrence on imaging was observed 9-24 months (median 11.5 months) postoperatively. Contrast-enhanced lesions were seen throughout or deeper into the luminal wall on imaging, but they were irregular and necrotic and were not well characterized by DWI/ADC due to strong perineural edema. Most of the patients had low density (around 15%) of tumor cells, but abundant T lymphocytes and foam cell infiltrate. 2 patients (9 and 20 months after the first surgery) showed no tumor cells, only necrosis, endothelial degeneration, and lymphocytic infiltrate, and were judged to have pseudoprogression. 1 patient (9 and 20 months after the first surgery) showed no tumor cells and was judged to have pseudoprogression. In one case (11.7 months after initial surgery), tumor-like dysplastic cells were found in less than 10% of the tissue. Discussion/Conclusion: When the first recurrence of glioblastoma after PDT is diagnosed, the possibility of late pseudo-progression should be taken into account, and the pathological search using various modalities such as MRS, perfusion study, PET/SPECT, etc. should be performed. Short-term wait and scan are important.